Influence of the flipped classroom on pedagogical management during distance education - Quinto-Román, Marino C. (2022)
The essential objective of this study was to demonstrate the incidence of the inverted classroom in the pedagogical management of the teacher of the Ramón Castilla Educational Institution of the Chuschi district, Cangallo, Ayacucho, Peru, 2021, during remote education. The research responds to a quantitative approach, experimental type, pre-experimental design. The data was presented through descriptive and inferential results. The main result was that the teachers, before applying the inverted classroom, appreciated their pedagogical management as regular (42.9%); after being implemented, they estimated it as good (61.9%) because it allowed the activities to be designed collaboratively. It is concluded that the inverted classroom has a significant impact on pedagogical management during virtual education.